IPTEK BAGI MASYARAKAT MESIN PENCETAK PELET UNTUK PAKAN TERNAK AYAM DAN LELE - Hasdiansah Hasdiansah; Erwansyah Erwansyah; Zaldy Sirwansyah Suzen; Dwi Ranti Safitri; Pristiansyah Pristiansyah (Pusat Penelitian dan Pengabdian Kepada Masyarakat, 2023)
The need for feed is very important for breeder, especially for chicken and catfish breeders in Indonesia with rapid development, for example breeders in Bangka Belitung to be precise in Sempan village. The high price of feed makes breeders process their own feed simply. In processing, breeders mice and mix the raw materials manually by hand and then ferment then overnight. From these problems, breeders need a machine that can refine feed raw material into one form of feed that is easily digested for livestock, such as pellets. Currently the processing of feed in the form of pellets can be used as an option. Therefore , a design and manufacture of a pellet molding machine was made for chicken and catfish feed with capacity of 10 kg/hour. The design method used in completing this final project is Verein Deutsche Ingineuer (VDI 2222) where this method is planned so that the actions taken are more directed and achieve the expected targets. Based on results of this design, a pellet molding machine design for chicken and catfish feed was obtained using electric motor with a power of 0.5 HP and rotation speed 1400 rpm with pulley and v-belt transmission and horizontal engine system using a screw as suppressor. From the trial results, the machine was able to print pellets with a diameter of 3 mm and 5 mm with capacity of 10 kg/hour.